2009
DOI: 10.1007/s11517-009-0447-y
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between salivary Chromogranin-A and stress induced by simulated monotonous driving

Abstract: Abstract:The purpose of the present study was to evaluate the use of salivary Chromogranin-A (CgA), which is already used in general as a mental stress marker, for studying the stressful situation created by simulated monotonous driving. After informed consent 25 healthy male & female subjects were studied, under constant environment-controlled conditions. We measured the following physiological variables: blood pressure (BP), cardiac output (CO), total peripheral resistance (TPR), normalized pulse volume (NPV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 33 publications
1
24
1
Order By: Relevance
“…However some studies showed inconsistent results (e.g., Yamakoshi, 2009). It might attributes to the nature of high "temporal sensitivity" of CgA against a mild stressor illustrated in our study.…”
Section: Profile Of Cgacontrasting
confidence: 51%
See 1 more Smart Citation
“…However some studies showed inconsistent results (e.g., Yamakoshi, 2009). It might attributes to the nature of high "temporal sensitivity" of CgA against a mild stressor illustrated in our study.…”
Section: Profile Of Cgacontrasting
confidence: 51%
“…CgA has been reported to transiently increase in response to short-term laboratory stressors such as a calculation test (Nakane, 1999), white noise (Miyakawa, 2006), and a cognitive task (Kanamaru, 2006). On the other hand there are studies failed to observe increase or rather decrease against a laboratory stressors (e.g., Yamakoshi, 2009) and observed a transient increase in subjects who declared the positive affection after watching a comic video (Toda, 2007).…”
Section: Salivary Cgamentioning
confidence: 99%
“…For example, salivary alpha amylase (sAA), which appears to capture components of sympathetic nervous system activity (Nater et al, 2005), is not reviewed; its role in response to stress has been reviewed separately elsewhere (Granger et al, 2007). Studies measuring salivary immunoglobulin A (sIgA), which plays an important role in mucosal immunity (Tsujita & Morimoto, 1999), and neuroendocrine markers like chromogranin A (CgA; Kanamaru et al, 2006; Yamakoshi et al, 2009) are also not reviewed here; biomarkers such as sAA, sIgA, and CgA are relevant to inflammation in the sense that the endocrine and sympathetic nervous systems are connected to the immune system, but are not themselves direct measures of inflammation (Nater & Rohleder, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…That is, all conditions exhibited the vascular-dominant reaction pattern, as indicated by the rise in TPR, which means that vasoconstriction occurred. In fact, this passive coping is a distinctive response in monotonous driving situations (Yamakoshi et al, 2013;Yamakoshi et al, 2009a;Yamakoshi et al, 2009b). However, compared with the two controls, MBP and TPR elevation is inhibited in 20Hz.…”
Section: Discussionmentioning
confidence: 86%
“…Driving tests were performed using a driving simulator, which had previously been constructed at Kanazawa University and validated in terms of usefulness as a simulator (Yamakoshi et al, 2009a;Yamakoshi et al, 2009b). The simulator consists of an adjustable car seat, steering wheel, gear lever, clutch, brake, and accelerator pedals for vehicle control.…”
Section: Measurement Quantities and Apparatusmentioning
confidence: 99%